Tobacco Economics in Myanmar - Kyaing, Nyo Nyo (World Bank, Washington, DC, 2013)
This study is based on different data sources but mainly on the Myanmar Study on Tobacco Economics 2001. Surveys of smoking prevalence in Myanmar show varying results, but most suggest that over 50% of the population over the age of 15 smoke, with figures being considerably higher among men than women. Cheroots are the most commonly used tobacco product (49% of all tobacco products consumed). Cheroots are produced locally either by cottage industries or by domestic companies. Recent trends in the price of tobacco products show that the real prices of all tobacco products have been declining. Econometric estimation shows that smokers are very sensitive to an increase in prices (price elasticity of demand is -1.62). In order effectively to reduce tobacco consumption, real prices of tobacco products need to be increased through heavier taxation, and other proven tobacco control measures need to be strengthened.